2018
DOI: 10.3390/s18082505
|View full text |Cite
|
Sign up to set email alerts
|

An Augmented Reality System Using Improved-Iterative Closest Point Algorithm for On-Patient Medical Image Visualization

Abstract: In many surgery assistance systems, cumbersome equipment or complicated algorithms are often introduced to build the whole system. To build a system without cumbersome equipment or complicated algorithms, and to provide physicians the ability to observe the location of the lesion in the course of surgery, an augmented reality approach using an improved alignment method to image-guided surgery (IGS) is proposed. The system uses RGB-Depth sensor in conjunction with the Point Cloud Library (PCL) to build and esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
(30 reference statements)
2
28
0
Order By: Relevance
“…One area of possible improvement for this AR system is in the degree of accurate registration between the virtual and physical models. Our average error of 2.47 millimeter, however, is similar to that demonstrated by other authors using comparable AR systems . In another study using the HoloLens platform by Wu et al, the average error was within 3 millimeters.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One area of possible improvement for this AR system is in the degree of accurate registration between the virtual and physical models. Our average error of 2.47 millimeter, however, is similar to that demonstrated by other authors using comparable AR systems . In another study using the HoloLens platform by Wu et al, the average error was within 3 millimeters.…”
Section: Discussionsupporting
confidence: 90%
“…Our average error of 2.47 millimeter, however, is similar to that demonstrated by other authors using comparable AR systems . In another study using the HoloLens platform by Wu et al, the average error was within 3 millimeters. Mahmoud et al reported virtual and physical model alignment of approximately 5 millimeters.…”
Section: Discussionsupporting
confidence: 90%
“…Achieving high-quality alignment is the critical step in model differencing, and CloudCompare's registration methods have been tested and used in the literature [26,[139][140][141]. The process is iterative, with the alignment becoming better with each iteration.…”
Section: Quantitative Differencing Using Cloudcomparementioning
confidence: 99%
“…Such systems require a large amount of high-resolution textures to provide an immersive sensation for users. Such high-resolution textures may even be required to be generated in real-time [4,5].…”
Section: Introductionmentioning
confidence: 99%